Question and answer
3. Is Mary Kay a global brand? Why or why not?
3. Is Mary Kay a global brand? Why or why not? Yes it is.. [ because Mary Kay brands expanded 30 markets on 5 continents Global Growth Quick Facts Mary Kay® products are sold in more than 35 markets worldwide, and the Company’s global independent sales force exceeds 1.8 million. Mary Kay Inc. has averaged double-digit growth since the Company’s founding in 1963. In 2007,
sales of Mary Kay® products reached $2.4 billion in wholesale sales. Since 1990, Mary Kay Inc. has experienced significant growth, opening in more than 20 new markets around the world. ]
Expert answered|vjmeneses01|Points 86|
Question
Asked 9/4/2013 10:34:02 PM
0 Answers/Comments
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
19,714,685 questions answered
Popular Conversations
Solve. -6b = -15
Weegy: -6b = -15 15 - 6b = 0 b = 5/2 User: Fill in the blank with the appropriate number. ____ - 39 = ...
3/1/2015 7:14:02 PM| 3 Answers
-6 + (-2)
Weegy: (-6)^-2 = 1/(-6)^2; = 1/36 User: 2/5*2/5
3/1/2015 7:42:50 PM| 2 Answers
Because the soil was depleted during the time of the Dust Bowl many ...
Weegy: moved westward to coastal states User: How did environmental changes in the Great Plains lead to changes in ...
3/1/2015 8:28:08 PM| 2 Answers
What group tends to define hackers and their activities in terms of ...
Weegy: Grey-hat hackers are those that may or may not do harm
3/1/2015 5:23:28 AM| 1 Answers
Which of the following describes the translation of the graph of y = ...
Weegy: x^2 has a negative coefficient so the parabola is opens downward. x-coordinate = 0/2(-1) = 0 ; since ...
3/1/2015 5:54:00 AM| 1 Answers
What is the solution set of x 2 + 5x - 5 = 0?
Weegy: 0.9(5x + 15) = 2.5 - (x + 3) 4.5x + 13.5 = 2.5 - x - 3; 4.5x + x = 2.5 - 3 - 13.5; 5.5x = -14; x = ...
3/1/2015 6:10:17 AM| 1 Answers
If (x + 1)(x - 3) = 12, then which of the following statements is ...
Weegy: x^2 - x - 12 = 0; (x - 4) (x + 3) = 0; x - 4 = 0; x = 4; x + 3 = 0; x - 3; x = {4, -3}
3/1/2015 6:16:37 AM| 1 Answers
Weegy Stuff
S
L
P
L
P
P
Points 78 [Total 7964]| Ratings 0| Comments 78| Invitations 0|Offline
S
P
C
L
P
L
1
Points 27 [Total 7334]| Ratings 0| Comments 27| Invitations 0|Online
S
1
L
L
Points 18 [Total 7519]| Ratings 0| Comments 18| Invitations 0|Offline
S
1
L
1
L
P
P
L
P
P
P
Points 9 [Total 16924]| Ratings 0| Comments 9| Invitations 0|Offline
S
Points 4 [Total 95]| Ratings 0| Comments 4| Invitations 0|Offline
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
S
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
S
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
S
Points 0 [Total 0]| Ratings 0| Comments 0| Invitations 0|Offline
Home | Contact | Blog | About | Terms | Privacy | Social | ©2014 Purple Inc.